The effect of 8 weeks aerobic exercise on severity of physical symptoms of premenstrual syndrome: a clinical trial study - Zahra Mohebbi Dehnavi; Farzaneh Jafarnejad; Somayeh Sadeghi Goghary (BMC, 2018)
Abstract Background Premenstrual syndrome (PMS) is a common disorder among women of reproductive age. Nearly 40% of women report problems with their menstrual cycles. Exercise is one of the recommended treatments to reduce symptoms of premenstrual syndrome (PMS). The present study was conducted to determine the effect of 8 weeks aerobic exercise on severity of physical symptoms of premenstrual syndrome (PMS). Methods This study was a randomized clinical trial (IRCT2015021721116N1) that was performed on 65 students living in student dormitories of Mashhad University of Medical Sciences in 2016, Iran. Samples were randomly assigned to control and intervention groups. The intervention group engaged in 8 weeks of aerobic exercises, three times a week, and 20 min for each session. The tools were research unit selection questionnaire, midwifery and personal particulars, temporary determination of premenstrual syndrome, Beck Depression, recorded daily symptoms of premenstrual syndrome and Borg scale. We analyzed the data using SPSS software and Mann-Whitney U test and Friedman test. Results At the beginning of the study, both control and intervention groups were homogeneous. The results of independent t-test showed that among the physical symptoms of the premenstrual syndrome in the intervention group compared to the control group, at the end of the study, headache (p = 0.001), nausea, constipation diarrhea (p = 0.01), swollen (p = 0/001) had a significant reduction. Also, the comparison of the difference between the mean of the signs at the beginning and the end of the study, bloating (p = 0.01), Vomiting (p = 0.002), hot flashes (p = 0.04), increase in appetite (p = 0.008) were significantly decreased. Conclusion Aerobic exercise as one of the ways to treat premenstrual syndrome can reduce the physical symptoms of the syndrome. Trial registration Name of registry: Zahra Mohebbi Dehnavi. IRCT registration number: IRCT 2015021721116 N1. Registration date: 2015 − 08-28. Registration timing: retrospective.